Numerical simulation study on the damage characteristics of water jet impact in drill holes with gangue coal rock - Yabin Gao; Shaoqi Zhang; Junyu Hong; Jing Cao; Mengbo Li (Scientific Reports)
Abstract In the context of coal mining, where gas problems are prevalent, water jet penetration enhancement technology has emerged as a critical solution for improving gas extraction. However, the presence of entrapped gangues in coal beds poses significant challenges to its effectiveness. This study analyzes the water jet impact damage characteristics in coal beds containing entrapped gangue using the Smooth Particle Hydrodynamics (SPH) method. The findings reveal that the gangue layer notably alters the crack propagation path, inhibiting the extension of main cracks on either side of the cone while promoting the formation of laminar and interconnected cracks. The findings reveal that the gangue layer notably alters the crack propagation path, inhibiting the extension of main cracks on either side of the cone while promoting the formation of laminar and interconnected cracks. Additionally, it affects stress wave propagation, leading to stress concentration in the upper portion of the gangue layer. During the water jet impact process, the changes in liquid-solid contact surface pressure are complex, with water hammer pressure, transition pressure, and stagnation pressure dominating different stages of the coal rock damage process. The reflective flow significantly enhances the cutting effect on the coal rock, achieving a peak velocity of up to 2.14 times the initial incident velocity. Moreover, increasing the distance, angle, and thickness of the gangue substantially complicates crack penetration, severely weakening the fracturing effect in the lower section of the gangue layer. Conversely, increasing the water jet pressure can effectively overcome the limitations posed by the gangue layer, significantly increasing the number of cracks and their expansion angles, thereby enhancing the overall fracturing degree of coal seams containing gangue and optimizing gas extraction conditions. The results of this research provide a crucial theoretical foundation for understanding the fracturing behavior of coal rock under complex geological conditions. Furthermore, they lay a solid groundwork for optimizing the drilling and water jet coal rock fracturing process, as well as for developing efficient gas extraction technologies.